Development of a Strategy for Business Improvement in the Cilembu Sweet Potato Chip Processing Industry (Case Study of the Small and Medium Enterprise “Ma Utik” in Cilembu Village, Pamulihan District, Sumedang Regency, West Java) - Inggid, Dwitya; Maulani, Rijanti Rahaju; Gunawan, Wawan (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
The SME “Ma Utik” is a household industry in Cilembu Village, Sumedang Regency, West Java, specializing in processing Cilembu cassava into chips. Despite its market potential, the SME faces challenges including limited production capacity, informal supplier partnerships, and ineffective marketing. This study aims to formulate strategies for the issue discussed by identifying supply chain conditions, evaluating business performance using key performance indicators (KPIs), and determining strategic priorities based on their influence within the system. A descriptive qualitative method was applied using three analytical approaches: Hayami analysis to measure cost efficiency and value added; KPI evaluation to assess five aspects—production, marketing, raw material supply, human resources, and finance; and the Analytical Network Process (ANP) to prioritize business improvement strategies. The results show that Ma Utik’s business system remains simple and unstandardized, with primary issues in production and marketing. Most performance indicators are still at the initial to intermediate stages, falling short of established targets. ANP findings highlight three key strategic indicators: distribution reach, process efficiency, and cassava raw material availability. The highest-priority strategy, with a score of 0.16, is Strategy C—developing digital marketing channels (e-commerce and social media). This strategy is deemed most relevant to expanding market reach and enhancing product competitiveness.